GREEN INFORMATION SYSTEMS IMPLEMENTATIONS, GREEN SUPPLY CHAIN MANAGEMENT PRACTICES, AND BUSINESS SUSTAINABILITY IN A DEVELOPING COUNTRIES CONTEXT: AN EMPIRICAL STUDY - Ahmed A. Zaid; Noor Qassas; Yahya Saleh; Luay Jum'a; Siraj Zahran; Mohammad Kanan; Abdalmuttaleb Al-Sartawi; Ramiz Assaf (Operational Research in Engineering Sciences: Theory and Applications, 2023)
While extensive literature examines the individual roles of green information systems (GIS) and green supply chain management (GSCM) in improving firm performance, there is a notable scarcity of studies exploring their combined impacts on business sustainability (BS) in developing nations. This study addresses this gap by investigating the direct connection between GIS implementations and BS in small- and medium-sized enterprises (SMEs) in Palestine. It also explores the mediating role of GSCM practices in this relationship. Data on GIS implementations, GSCM practices, and factors related to BS were collected through a survey and analyzed using partial least squares structural equation modeling (PLS-SEM). The results demonstrate that GIS implementations have a positive and significant impact on GSCM practices and BS. Moreover, the relationship between GIS implementations and BS is significantly mediated by GSCM practices. This research is distinctive in its examination of the effects of GIS and GSCM on BS within the context of a developing country, providing valuable insights to the literature and presenting new perspectives on achieving sustainable performance in complex business environments.